Stress-free discipline : simple strategies for handling common behavior problems - Au, Sara (American Management Association (AMACOM), 2015)
"All children test boundaries (and sometimes your patience). It's a natural part of growing up. Your job as a parent is to let them know what's acceptable and what isn't, praise good behavior, and enforce limits. Easier said than done. Even the best-intentioned parents can find themselves shouting--or capitulating yet again to avoid a scene. Worse, the one-size-fits-all discipline methods experts tout can be too narrow for some concerns. Blending developmental insights with an arsenal of proven techniques, Stress-Free Discipline prepares parents for any challenge: the preschooler who throws a fit ... the second-grader who refuses homework ... the budding tween who dishes out insults. The book helps determine the root cause, explaining what drives the behavior, why it's usually normal, how to prevent escalations, and how to instill self-control. Once parents grasp the underlying motivation they can select the strategy that fits their child's age, temperament, and issue--including role modeling, setting limits, positive reinforcement, negative consequences, disengagement--and deploy it calmly and with confidence. Examples and exercises throughout help readers personalize the authors' advice to their unique situation. Practical, thoughtful, and deeply informative, Stress-Free Discipline is the one book every family needs for a more peaceful and happy home."